Lsm Proteins Are Required for Normal Processing of Pre-tRNAs and Their Efficient Association with La-Homologous Protein Lhp1p - Kufel, Joanna (American Society for Microbiology, 2002)
Depletion of any of the five essential proteins Lsm2p to Lsm5p and Lsm8p leads to strong accumulation of all tested unspliced pre-tRNA species, as well as accumulation of 5′ and 3′ unprocessed species. Aberrant 3′-extended pre-tRNAs were detected, presumably due to stabilization of transcripts that fail to undergo correct transcription termination, and the accumulation of truncated tRNA fragments was also observed. Tandem affinity purification-tagged Lsm3p was associated with pre-tRNA primary transcripts and, less efficiently, with other unspliced pre-tRNA intermediates but not mature tRNAs. Association of the Saccharomyces cerevisiae La homologue Lhp1p with pre-tRNAs was reduced approximately threefold on depletion of Lsm3p or Lsm5p. The association of Lhp1p with larger RNA polymerase III transcripts, pre-RNase P RNA and the signal recognition particle RNA (scR1), was more drastically reduced. The impaired pre-tRNA processing seen on Lsm depletion is not, however, due solely to reduced Lhp1p association as evidenced by analysis of lhp1-Δ strains depleted of Lsm3p or Lsm5p. These data are consistent with roles for an Lsm complex as a chaperone that facilitates the efficient association of pre-tRNA processing factors with their substrates.